Tradycja w języku - Aleksander Wilkoń (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2011)
The paper attempts to analyze the notion of tradition and determine its place within the historical linguistics. The first part presents established definitions and typologies of tradition whereas the second – the author’s understanding of the concept and a model of linguistic text analysis which aims at demonstrating how tradition manifests itself in language. The model is applied to the analysis of famous lament by Jan Kochanowski.